The Study and Review of Localization Techniques on Wireless Sensor Networks - Sruthi, Pinamala; K. Sahadevaiah, Dr. (International Journal of Engineering and Technology, 2018)
Localization is an active field of research in Wireless Sensor Networks (WSNs) to identify the current location of the sensor nodes. A WSN consist of thousands of nodes that make the installation of GPS on each sensor node expensive and moreover GPS will not provide exact localization results in an indoor environment. Manually configuring location reference on each sensor node is also not possible in the case of dense network This gives rise to a problem where the sensor nodes must identify its current location without using any special hardware like GPS and without the help of manual configuration. Localization techniques make the deployment of WSNs economical. Most of the localization techniques are carried out with the help of anchor node or beacon node, which knows its present location. Based on the location information provided by the anchor node or beacon node, other nodes localize themselves. In this paper we present a succinct survey on the localization techniques used in wireless sensor networks covering its problems and research gap.
Keywords: Localization; Wireless Sensor Network; Range Free; Range Based; Anchor node; un-localized node; Beacons; TOA; TDOA; RSSI; AOA; ADLA.